2019
DOI: 10.3390/ijms20092172
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Ash Mineral Extract Increases Pigmentation through the p-ERK Pathway in Zebrafish (Danio rerio)

Abstract: The purpose of the present study is to evaluate the effect of rice bran ash mineral extract (RBM) on pigmentation in zebrafish (Danio rerio). Melanin has the ability to block ultraviolet (UV) radiation and scavenge free oxygen radicals, thus protecting the skin from their harmful effects. Agents that increase melanin synthesis in melanocytes may reduce the risk of photodamage and skin cancer. The present study investigates the effect of RBM on pigmentation in zebrafish and the underlying mechanism. RBM was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Spotless watermeal (Wolffia arrhiza) was found to be very effective in the enhancement of pigmentation in queen loach (Botia dario) when incorporated at the dose of 150 g/ kg of diet along with 25 g/kg of spirulina [17]. According to Kim et al [30], rice (Oryza sativa) bran mineral induce pigmentation in zebra fish (Danio rerio) through ERK signalling pathway and ERK phosphorylation. Investigation proved that supplementation of diet with 5-10% of apple (Pyrus malus) peel meal provides great pigmentation in snow trout (Schizothorax richardsonii) [28].…”
Section: Shoe Flower 5% Of Hibiscus Powder Petal Meal Xiphophorus Hellereimentioning
confidence: 99%
See 1 more Smart Citation
“…Spotless watermeal (Wolffia arrhiza) was found to be very effective in the enhancement of pigmentation in queen loach (Botia dario) when incorporated at the dose of 150 g/ kg of diet along with 25 g/kg of spirulina [17]. According to Kim et al [30], rice (Oryza sativa) bran mineral induce pigmentation in zebra fish (Danio rerio) through ERK signalling pathway and ERK phosphorylation. Investigation proved that supplementation of diet with 5-10% of apple (Pyrus malus) peel meal provides great pigmentation in snow trout (Schizothorax richardsonii) [28].…”
Section: Shoe Flower 5% Of Hibiscus Powder Petal Meal Xiphophorus Hellereimentioning
confidence: 99%
“…Studies have shown that zebrafish embryo when treated with extract of rice bran ash stimulates and enhances melanin biosynthesis by positively affecting the transcription factors. Melanin production directly effects hypopigmentation, forage free radicals, blocks the entry of UV radiation and thereby prevent skin damage as well as skin cancer [30]. When oliver flounder was fed with diet-containing paprika extract, increased radical foraging activities were observed in the muscles, plasma and liver [40].…”
Section: Associative Parametersmentioning
confidence: 99%
“…Melanin is synthesized from a process called melanogenesis, which is a rather complex metabolic pathway that combines spontaneous chemical and enzymatically catalyzed reactions [83]. Several studies have focused on the prevention of depigmentation or hyperpigmentation in the skin by regulating the process of melanogenesis [84]. In this context, zebrafish have been used extensively to assess in vivo the pigmenting or depigmenting activity of melanogenic regulatory compounds.…”
Section: Study Of the Effect On Pigmentation In Zebrafishmentioning
confidence: 99%
“…Vertebrate melanocytes almost always originate from the neural crest, and the cells derived from the neural crest undergo obvious differentiation until they are dispersed, and produce peripheral neurons, glial cells and melanocytes at precise locations [36]. Furthermore, phosphorylation of ERK in MAPK signaling pathway inhibits the production of melanin in zebrafish, while inhibition of phosphorylation of ERK can promote the production of melanin in zebrafish by increasing the expression of MITF genes, thereby upregulating downstream genes TYR, TRP1 and TRP2 [37]. The expression of MITF was also able to differentiate pluripotent stem cells into melanocytes in medaka [38].…”
Section: Regulated Genes In Brown Skin Indicated the Molecular Mechan...mentioning
confidence: 99%